2009
DOI: 10.1021/jp900775b
|View full text |Cite
|
Sign up to set email alerts
|

Shape Control of Silver Nanoparticles by Stepwise Citrate Reduction

Abstract: Growth of silver nanoparticles by the citrate reduction of silver nitrate under the range of pH from 5.7 to 11.1 was investigated systematically and quantitatively. Reduction of the silver precursor (Ag + ) was promoted with increased pH, attributed to the higher activity of the citrate reductant under high pH value. Under high pH, the product was composed of both spherical and rod-like silver nanoparticles as a result of the fast reduction rate of the precursor. Under low pH, the product was mainly dominated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
232
0
9

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 315 publications
(260 citation statements)
references
References 36 publications
13
232
0
9
Order By: Relevance
“…2). Any influence of the cations in the chloride salts can be excluded since replacing NH 4 Cl Akin to citrate [36], hydrazine has a higher reduction activity at high pH values. Directly adding hydrazine solution to the AgNO 3 solution containing PVP (the original pH value was about 4.7) led to an increase in the pH of the reaction system, due to the alkaline nature of hydrazine, itself and afforded spherical Ag nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
“…2). Any influence of the cations in the chloride salts can be excluded since replacing NH 4 Cl Akin to citrate [36], hydrazine has a higher reduction activity at high pH values. Directly adding hydrazine solution to the AgNO 3 solution containing PVP (the original pH value was about 4.7) led to an increase in the pH of the reaction system, due to the alkaline nature of hydrazine, itself and afforded spherical Ag nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
“…41 Silver nanoparticles of very different geometric (size and shape) characteristics can be obtained by modifying the reaction conditions. 42 It is recognized that the preparation method influences the interactions of the silver nanoparticles with living organisms; therefore, the nanoparticles can be tuned to the required application through controlling the synthetic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Ledwith et al [24] used silver seeds to produce triangular platelets of different sizes by controlling the concentration of sodium citrate as well as the temperature of the synthesis [24]. Dong et al showed that controlling the pH of the reaction solution permits the control of the size and morphology of silver nanoparticles [25]. Dong et al [26] also reported the stepwise reduction of silver nitrate with sodium borohydride (NaBH 4 ) and trisodium citrate in an ice bath for 30 min, after which they heated the solution to 70 C to trigger the remaining silver nitrate to obtain triangular silver nanoprisms.…”
Section: Introductionmentioning
confidence: 99%